Evaluation of corporate management: costs by activity (abc costs) - Vergiú Canto, Jorge (2001)
In the decade of the 80's thaks to the Prof. Robert Kaplan and to the Prof. Thomas Jhonson was created the concept of finance based on activities which allows us to provide to the company costs more precise products. No only methodology of costs can be present in a production companies but also in companies of services based in that all company for the abtaining of its products goes by diverse administration processes.